The Role of Accounting and Risk Management in Supply Chain Management: A lesson learnt from the Indonesian Meat Industry - Irma Setyawati (International Journal of Supply Chain Management, 2018)
Now a day, supply chain management (SCM) has been continuously imperative. Supply chain management performs is developed up. A significant number of studies were centered around supply chain management in the scholarly community. The motivation behind this investigation of study is to inspect the part of risk management on upgrading the execution of supply chain management, to look at the capacity of accounting management on expanding the execution of supply chain management, to reinforce the moderating part of information technology between risk management and supply chain management and to fortify the moderating part of information technology between accounting management and supply chain management. To accomplish these destinations, the present investigation utilized quantitative approach. Study strategy used to gather the information. Information were gathered from workers of Indonesian association of meat provider. Three hundred (300) samples were appropriated among the respondents. After analyzing the information through Smart PLS 3, it was discovered that meat providers and meat providers have been moving and centering towards decreasing cost, upgrading productivity and viability of supply chain management framework. In addition, it was explored that for decreasing cost and improving execution accounting management programming is fundamental. Further, information technology is the beneficial choice to decreased risk and enhancing the effectiveness of supply chain management in Indonesian association.